Sustainable Routes and Mechanistic Study in Pyrazole Synthesis Using Deep Eutectic Solvents (DESs) - Aheer, Ashish Kumar; Choupra, Kanaram; Jain, Meenakshi; Sharma, Amit (Sustainability & Circularity NOW, 2025)
Increasing demand for green and sustainable chemical processes has led to new investigations in organic synthesis. One of the significant groups of heterocyclic compounds, pyrazoles, finds widespread use in materials science, agrochemicals, and medicines. Pyrazoles have been synthesized using various volatile organic solvents by conventional methods. Due to their enormous importance, sustainable synthetic methods using various green solvents have been developed by researchers. This work focuses on the recent developments in green chemistry, particularly, for the production of pyrazole derivatives using deep eutectic solvents (DESs). DESs are biodegradable, low toxic, and have the ability to dissolve a wide range of organic and inorganic compounds. These properties can offer a more environmentally friendly option than the negative effects of traditional synthetic methods. The benefits of DES in pyrazole synthesis include accelerated reaction rates, high selectivity, and minimum solvent reaction conditions in DES. Moreover, we have summarized various mechanistic insights, optimization of the reaction, and practical applications of DES in pyrazole chemistry. This review article is designed to give a systematic overview of DES-mediated pyrazoles’ synthetic techniques with insightful information.
Keywords: Deep eutectic solvents; Sustainable processes; Pyrazoles; Green synthesis; Bio-vital heterocycles; N-Heterocycles